Impact of chemical shock loads on a membrane bioreactor for urban wastewater reuse - Knops, Geraldine Jane Augustine (Cranfield University, 2010)
The performance of an MBR under chemical shock loading conditions was investigated, to ascertain the robustness of the treatment system for urban water reuse. 32 household products and industrial substances, likely to be found in urban wastewater were assessed for toxicity, using Microtox and respirometry to obtain EC50 values. Six of these toxins were dosed into bench scale porous pots to observe any detrimental effects on the treatment system, in terms of effluent quality and potential foulant release. Four toxins were dosed into a pilot scale MBR to observe the effects of scale and enhanced biomass retention on the perturbations seen at bench scale. Mitigation of the foulants observed was investigated by the addition of ancillary chemicals. 10 household products and 6 industrial products were identified as being of risk to a biological treatment system with EC50 concentrations of the order that could be present in urban wastewater. 2 of the 6 toxins dosed into the porous pots caused a serious impact on the system reducing COD removal rates to 45%, compared with 92% average for the control pots, and increasing SMP turbidity to 11 NTU. 1 of the 4 toxins dosed into the MBR caused an impact, although less than observed in the porous pots, with the COD removal rate reducing to 77% and SMP turbidity increasing to a maximum of 9 NTU. Jar tests carried out to investigate mitigation potential of SMP turbidity found the cationic polymers MPE50 and high molecular weight polyDADMAC most efficient with reductions of SMP turbidity to <1 NTU possible although the toxins increased the dose necessary to achieve this.
Keywords: chemical shock loading; MBR for reuse; unsteady state operation; chemical mitigation